A Study on the Relationship between English Language Proficiency and Intercultural Communication Competence among Arab Students in Malaysia - Sarwari, Abdul Qahar; Muhammad Nubli, Abdul Wahab (Arab Society of English Language Studies (ASELS), 2018)
This study was carried out to evaluate the relationship between English language proficiency (ELP) and intercultural communication competence (ICCC) of Arab students in Malaysia. This study included both of the quantitative and the qualitative data sets to further the information. The participants of this study were 108 Arab students from nine different Asian and African nationalities. Based on the results of this study, English language was the main means of education for the participants, and the main means of their communication with students from other cultures. The results from this study found some significant correlations between the attributes of ELP and ICCC. The good levels of ELP encouraged and enabled individuals to be involved in daily interactions with their peers from different countries who speak different languages, and their interactions helped them to improve the levels of their ELP. Moreover, the participants who obtained higher scores in English language proficiency test got higher mean scores in ICCC as well. Based on the results, in some cases, their personal characteristics and the low levels of their ELP had negative effects on the process of interactions among Arab and other students. The results of this study may add some interesting information in the literature regarding the relationships between ELP and ICCC of Arab students in an Asian multicultural collegiate environment.